ANALYSIS OF ENGLISH COMMUNICATION DISORDERS IN STUDENTS OF THE ENGLISH EDUCATION PROGRAMM OF IAIN BONE: PSYCHOLINGUISTIC PERSPECTIVE - Nursidah, Nursidah (Univeristas Islam Negeri (UIN) Alauddin Makassar, 2023)
The existence of Psycholinguistics as a scientific discipline which has as an object of study the various psychological processes that underlie human communication, both in terms of producing language and perceiving it, has provided an alternative perspective in understanding various human communication disorders using English as the language of instruction. Communication disorders when producing language consist of phonetic, morphological, lexical and syntactic disorders while communication disorders when perceiving language consist of problems understanding the pronunciation of words from the interlocutor, problems understanding categories of expressions with their meaning, and problems understanding between verbal and non-verbal language. Factors that cause English communication disorders among students of the IAIN Bone Tadris English Study Program from a Psycholinguistic perspective are the mixing of students' first and second languages or foreign languages in the communication process, the students' limited ability and their confidence in communicating in English, as well as students' use of English is not yet intensive. Special strategies are needed to deal with these various communication disorders by exploiting the intersection between existing languages and growing students' ability and confidence in speaking English.